Influence of feasibility of motivational strategies development perceived by teachers on students’ motivation in Physical Education (Agora for Physical Education and Sport, 2018)
The objective of this work was to analyze the feasibility of developing certain motivational strategies designed to foster basic psychological needs satisfaction perceived by physical education (PE) teachers. Furthermore, it was aimed to check whether these perceptions could affect basic psychological needs, self-determined motivation, liking for PE and importance of PE perceived by students. The study sample consisted of 66 PE teachers (M = 42.12; DT = 9.29) and 1577 Secondary Education students (M = 15.11; DT = 1.72) from three countries. An ad hoc questionnaire to measure feasibility of motivational strategies was administered to teachers, while students completed some previously validated instruments. Teachers perceived strategies oriented to foster autonomy to be less feasible than strategies oriented to foster competence or relatedness. On the other hand, Mann-Whitney test revealed that students whose teachers scored higher in general feasibility of motivational strategies showed higher scores in self-determined motivation, autonomy, competence and importance of PE. These findings suggest the need for implementing training programs among teachers. It could foster teachers’ competence to develop methodological strategies which might be effective to facilitate adaptive motivational patterns among students.
Keywords: Motivational strategies; teachers' antecedents; physical education; self-determination theory; motivation